Assessing fracture risk (FRAX) and falls risk among the elderly in a specialist primary care clinic in Klang Valley, Malaysia / Mohd Yusaini Mohd Yusri ... [et al.] - Mohd Yusri, Mohd Yusaini; Ariffin, Farnaza; Isa, Mohamad Rodi; Mat Nasir, Nafiza (Faculty of Medicine, 2024)
Introduction: The fracture risk assessment (FRAX) is a tool to assess the fracture risk among the elderly. However, FRAX does not include other domains of fall risk and this can be assessed using the falls risk assessment tool (FRAT). The study looks to compare the FRAX and FRAT tools, as well as the prevalence of fall risk and fracture risk and factors associated with high risk of fracture. Methods: This was a cross-sectional study among elderly patients aged 60 years and above who attended a specialist primary care clinic. The study tool included the sociodemographic and clinical characteristics details of the participants and the FRAX and FRAT assessment. Data were entered and analysed using SPSS version 23. Results: A total of 307 participants were analysed with a mean age of 68.1 (SD=6.1). The prevalence for high fracture risk and high fall risk was 23.5% (95% CI: 18.7, 28.2) and 26.7% (95% CI: 21.7, 31.7) respectively. Six factors were found to be associated with high fracture risk. These six factors were higher age group (P<0.001), non-Malay ethnicity (P=0.004), patients on calcium supplements (P=0.003), medical history of gout (P=0.048), lower BMI categories (P<0.001) and history of previous fracture (P<0.001). The study also found that there was no correlation between FRAX and FRAT calculation [κ = 0.10 (95%CI: -0.02, 0.21), P=0.079]. Conclusion: FRAX calculation predicts fracture risk but does not include all of the domains of fall risk. Clinicians need to assess fall risk (FRAT) on top of the FRAX among the elderly for a more accurate fracture risk assessment.